Profile of Conceptual Understanding of Trigonometric Identities in Grade 11 at Madani Integrated Model Public High School in Palu, Examined by Gender and High Mathematical Ability - Dina Noviandri Djaanggeli; Tegoeh S Karniman; Rahma Nasir; Muh. Rizal (Journal of Educational Sciences, 2026)
This study aims to describe the profile of students’ conceptual understanding of trigonometric identities in terms of gender among students with high mathematical ability. This is a descriptive study using a qualitative approach. The research subjects consisted of two 11th-grade students at Madani Palu Integrated Model Public High School: one female student and one male student who demonstrated high mathematical ability based on their report card grades and teacher recommendations. Research data were collected through a written essay-style test and semi-structured interviews, then analyzed using the Miles, Huberman, and Saldana model, which includes data condensation, data presentation, and drawing conclusions. Data validity was tested using the member check technique. The results of the study indicate that both subjects were able to meet the four indicators of conceptual understanding: restating concepts, classifying objects according to their properties, using and selecting appropriate procedures, and applying concepts or problem-solving algorithms. The female student tended to be more systematic in her problem-solving steps, while the male student demonstrated a broader and more efficient ability to relate concepts to one another. Thus, both groups demonstrated a good conceptual understanding of trigonometric identities, with distinct characteristics based on gender.